Encapsulation of Walnut Oil in Urea-Formaldehyde for Self-Healing Coating: Effect of Mixing Speed - Suyatmo, Reviana Inda Dwi; Topandi, Abdussalam; Gultom, Indah Gita Cahyani; Nulhakim, Lukman (Sainteknol : Jurnal Sains dan Teknologi, 2023)
Self-healing coating is a technology where repairation of a coating can be done automatically. The self-healing agent is encapsulated in the form of microcapsules. When the microcapsules or shell material breaks, the healing agent released onto the damaged surface. In this study, walnut oil was used as a healing agent because it belongs to the drying oil which has been widely used as a coating. The polymer used as the microcapsule shell is urea-formaldehyde. This research was conducted to examine the effect of mixing speed on the diameter and thermal stability of microcapsules encapsulated by walnut oil in urea formaldehyde, as well as to see the self-healing performance. The results of FTIR testing proved that the microcapsules consist of Poly Urea Formaldehyde (PUF) as a shell material. The research showed that the mixing speed of 860 rpm produced microcapsules with the smallest diameter of 90.1426 micrometer and the highest decomposition temperature of 362.38°C. The results of self-healing tests on steel plates prove that the healing agent used has succeeded in repairing the damage by covering the surface of the scratched sample.